An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Vinueza, Luis (2010)
This research work about the Suitability of Selected Newspaper Material as a Teaching Resource in EFL Courses as a guide by teachers since it contains information about the importance and usability of newspapers to teach English. In fact, the articles, reports, news and ads taken from The New York Times, New York Post, USA Today, and the International Herald Tribune newspapers have interesting examples of grammatical structures, vocabulary, presented in context with a formal style that let teachers use these selected newspapers for engaging students in active English learning.